Psychosocial hierarchies of modifiable risk for Alzheimer’s disease: A networks analysis - James John Rochfort Brady; Larissa Bartlett; Eddy Roccati; Kimberley Norris; James Clement Vickers; Duncan Sinclair (PLoS ONE, 2026)
Thirty per-cent of multidomain risk reduction trials for Alzheimer’s disease and related dementias (ADRD) report limited efficacy. Identifying potential cascading influences between psychosocial ADRD risk factors is a promising strategy for increasing this efficacy rate. We aimed to identify relational hierarchies among modifiable ADRD risk factors to inform temporally optimized prevention strategies. We applied a dual network approach—regularized partial correlation network (RPCN) and a Bayesian directed acyclic graph (DAG) generated via a novel ensemble method—to cross-sectional data from 898 community-dwelling older adults enrolled in an ADRD prevention initiative. The RPCN revealed clustering among mental health domains. The DAG suggested directional associations from stress, anxiety, and coping to downstream factors including depression, social support, cognitive activity, and cardiometabolic domains (physical activity, BMI, blood pressure, and MIND diet adherence). This dual-network framework highlights upstream psychosocial factors statistically associated with multiple ADRD-related risks. Models suggest targeting stress and coping may offer broad, cascading, benefits for ADRD risk reduction. Further exploration of strategically staggered and/or needs-based individualization of future modifiable ADRD prevention initiatives is warranted.